Relação entre macrofauna, agregação e atributos edáficos em sequência de culturas sob plantio direto - Batista, Itaynara [UNESP] (2015)
The no-tillage system (NT) is presented as an agricultural technique that improves the chemical, physical and biological soil properties. However, many questions still remain as to the effect of the type and sequence of cultures on plantsoil- organisms interactions. The objective of this study was to investigate the effect of crop sequences in no-tillage system in the community of soil macrofauna and chemical and physical characteristics of aggregates in two evaluation periods, dry and wet in areas of morphological domain of Atlantic Forest. The hypotheses tested were: e) crop rotation with species of grass/legumes (corn/soybean) favors the formation of aggregates of different morphological types with different physical and chemical characteristics, due to the action of roots and food selection by soil macrofauna; ii) the evaluation period promotes changes in the environment for the formation of aggregates due to the recent culture and seasonality; iii) biological agents (macrofauna and roots) alter the dynamics of organic matter associated with soil aggregates due to food selection by macrofauna and action of roots; iv) the rotation of grass/legumes promotes greater richness of individuals, uniformity of soil macrofauna, greater abundance of groups decomposers of organic matter and engineers of the ecosystem when compared to grasses or legumes, due to improvement in the availability of food resources. The experiment was conducted under NT in Jaboticabal - SP, the treatments analyzed were: soybean monoculture (legume) in the summer and sun hemp (legume) in the off season (S-SH), corn monoculture (grass) in the summer and corn in the off season (C-C), rotation soybean/corn in the summer and a corn in the off season (S/C-C) and rotation soybean/corn in the summer and sun hemp in the off-season (S/C-SH). The sampling was carried out in August 2012 and March 2013. ...